(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:In the current article, a compound based on copper and tungsten trioxide was used at a rate of 5%, and it was reinforced with nano-tungsten carbide in volumetric percentages (0,5,10,15,20%). The powders were mixed by the volumetric method due to the difference in density between the three powders. The grinding was done for 2 hours with a homemade mill and steel rollers. After that, the mixed powders were pressed with a hydraulic press of Turkish origin with a pressure of (5 tons) for one minute. The prepared samples were sintered at 900°C for 2 hours only. In addition, various tests were carried out on the samples, including (true density, true porosity, compressive strength, wear, scanning electron microscope) before and after sintering. The results showed that the best mixing ratio was 20% after sintering, which gave the best true density (313.720 g/cm) and the least porosity (10.310%), while the highest compressive strength reached (125.70 N/mm2), and the least slip wear was obtained by (2.01 * 10-6 g / cm). As for the results of scanning electron microscopy (SEM) and X-ray spectroscopy (EDS), we showed the appearance of a homogeneous surface of metal, oxide and nano-carbide, which was spread through the copper ground, which improved the physical and mechanical properties, which was shown through EDS.Keywords: nanotungsten carbide, porosity, compressive strength, heat treatment.